Two-dimensional heterometallic CuIILnIII (Ln = Tb and Dy) coordination polymers bridged by dicyanamides showing slow magnetic relaxation behavior. Issue 34 (6th August 2019) - Kong, Jiao-Jiao; Zhang, Jia-Chen; Jiang, Yu-Xuan; Tao, Jin-Xia; Wang, Wen-Yan; Huang, Xing-Cai
Abstract : Two-dimensional heterometallic Cu II Ln III (Ln = Gd, Tb and Dy) coordination polymers bridged by dicyanamides showed slow magnetic relaxation behaviour and a magnetic hysteresis loop at 1.8 K was observed for the CuTb compound. Abstract : Using dicyanamides, three two-dimensional coordination polymers (CPs) [Cu II (valdmpn)Ln III (μ-1, 5-dca)3 ] n (Ln III = Gd (1 ), Tb (2 ) and Dy (3 )) were synthesized and characterized. Compounds1–3 are two-dimensional coordination polymers bridged with μ-1, 5-dca connecting the [Cu II (valdmpn)Ln III ] 3+ units. In compounds1–3, the Cu atom was pentacoordinated with an elongated square pyramidal ( C 4v ) geometry, while the Ln (Gd, Tb and Dy) atom was nine-coordinated with a muffin ( C s ) geometry. Detailed direct current (dc) magnetic measurements and simulated data demonstrated the existence of a ferromagnetic Cu II –Gd III interaction for compound1 . Alternating current (ac) magnetic measurements revealed that compound2 exhibited a slow magnetic relaxation behavior under a zero dc field. A hysteresis loop at 1.8 K was observed in compound2, characteristic of typical single-molecule magnets (SMMs). However, compound3 showed a slow magnetic relaxation behavior under a dc field. This system provides a good opportunity to determine the character of the Ln(iii ) ions incorporated and/or the origin of the slow magnetic relaxation behavior.